Skill development and youth aspirations in India - Nambiar, D (2014)
This doctoral thesis features two kinds of skill-training programmes implemented in Tamil Nadu (India) drawing on 18 months of fieldwork. The first explores how Nokia recruits and trains semi-skilled youth to work as Operators, in the Nokia SEZ, in Sriperumbudur. I contrast this with the case of Project SEAM: a state-funded skill-training programme, implemented by a private firm through a public-private partnership (PPP). SEAM trains rural, below-poverty-line youth, to work as sewing machine operators in India’s burgeoning garment clusters. I argue that contemporary India’s development trajectory is characterised by the confluence between an increasingly pluralised network state and rapidly proliferating network enterprises, which work together to establish new workplaces and design and implement skill-training programmes for India’s rural poor. Skill-training is used as a lens to examine the complex, symbiotic relationship between these two actors, who drive these new initiatives. Skill development programmes are predicated on the idea that aspiration is a positive, transformative force – a view that is echoed by social scientists like Appadurai (2004; 2013). I demonstrate how the network state and network enterprise, shape and mould youth aspirations, across the skill-training cycle: transforming (within mere weeks) unemployed, unskilled rural youth – into semi skilled workers, ready to work in the manufacturing sector. Youth aspirations are consciously heightened as a marketing strategy, to maximize enrollments into skill-training programmes. Aspiration is also actively taught as a valuable soft-skill, that young people must possess, to become a part of India’s new workplaces. Through an exploration of how young people encounter such initiatives, I question the idea that aspirations are positively transformational. I highlight the tension in youth experience - between aspirations elevated by the training program, and factory work’s harder realities - to illustrate the dark side of aspiration: characterized by disillusionment, disappointment and personal failure.